2014
DOI: 10.1149/06127.0249ecst
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Diagnostics Applied to a Self-Breathing Fuel Cell

Abstract: In a self-breathing fuel cell, oxygen is taken directly from ambient air which provides the benefit of reduced system complexity and system operation. This study explores the use of, printed circuit boards (PCBs) as flow field plates to design a self-breathing fuel cell which helps reduce overall volume and cost of the system. It investigates the effect opening ratios have on fuel cell performance using polarization curves and electrochemical impedance spectroscopy. The result obtained indicates that greater o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Thermocouples can provide a crude measure of temperature inside fuel cells [15][16][17][18], but cannot provide high spatial resolution, and as they need to be inserted inside the fuel cell, this often requires design modifications which may affect reactant flow and fuel cell performance. Infrared thermal imaging can provide very high spatial and temperature resolution [19][20][21][22][23][24], but requires use of modified fuel cells with an infrared transparent window, and/or cells with open channels (such as open-cathode fuel cells [25][26][27][28]) or can only image the outer surface of a cell or stack [29,30]. Combined temperature and current mapping studies allow the impact and interactions of these two parameters on the overall performance to be assessed [17,20,[31][32][33].…”
Section: Current and Temperature Mapping In Fuel Cellsmentioning
confidence: 99%
“…Thermocouples can provide a crude measure of temperature inside fuel cells [15][16][17][18], but cannot provide high spatial resolution, and as they need to be inserted inside the fuel cell, this often requires design modifications which may affect reactant flow and fuel cell performance. Infrared thermal imaging can provide very high spatial and temperature resolution [19][20][21][22][23][24], but requires use of modified fuel cells with an infrared transparent window, and/or cells with open channels (such as open-cathode fuel cells [25][26][27][28]) or can only image the outer surface of a cell or stack [29,30]. Combined temperature and current mapping studies allow the impact and interactions of these two parameters on the overall performance to be assessed [17,20,[31][32][33].…”
Section: Current and Temperature Mapping In Fuel Cellsmentioning
confidence: 99%
“…otherwise confined to open-cathode fuel cells [23][24][25] or the outer surface of a cell or stack [26,27].…”
Section: Current and Temperature Mapping In Fuel Cellsmentioning
confidence: 99%
“…This mode of operation can also be used as a diagnostic-identifying areas of high or low electrochemical activity, thus elucidating vital information in the design and optimisation of systems. Air breathing PEMFCs were examined by Obeisun et al [39] who looked at the temperature distributions, shown in Figure 2, associated with the passive fuelling strategy employed by these devices. An increased operating current was seen to result in increased surface temperatures, with inhomogeneous distributions being imposed on the device by the housing in which it was contained.…”
Section: Single Frame Imagingmentioning
confidence: 99%
“…The effect of clamping pressure was also observed to have an impact on the temperature distribution; with lower clamping pressures in the center of the cell resulting in a lower temperature, this was attributed to poor electrical contact. Images showing the effect of the opening ratio (i.e., the area of electrode exposed to the atmosphere) of an air breathing PEMFC obtained by Obeisun et al [39]. Heterogeneous temperature distribution is clearly visible on the cell due to non-uniform clamping forces and the flow configuration in the system.…”
Section: Single Frame Imagingmentioning
confidence: 99%
See 1 more Smart Citation